Peran Digitalisasi Dalam Transisi Akuntansi Profesional Menuju Era Teknologi - Ni Luh Anik Listya Wati; Shabrina Maulida; Anak Agung Erna Trisnadewi; Cynthia Cynthia (Lembaga Penelitian, Universitas Warmadewa, 2025)
The development of digital technology has had a major impact on the world of the development of digital technology has revolutionized various aspects of life, including the accounting profession which is now no longer dependent on manual recording. This change encourages accountants to adopt information technology in their daily practices. This study aims to analyze the role of digitalization in the transition of the accounting profession and identify relevant challenges and adaptation strategies. The study uses a qualitative approach with a literature study method, which allows for in-depth exploration of previous theories and findings. Data analysis was carried out through content analysis of various scientific sources. The results of the study indicate that digitalization drives significant changes in the role of accountants, from transaction recorders to strategic analysts. Technology accelerates accounting efficiency and accuracy, but the level of readiness to face digital transformation still varies, especially among MSMEs. The main challenges include low digital literacy, limited infrastructure, and lack of advanced technology skills. Effective adaptation strategies include ongoing training, curriculum reform, and assistance in the use of financial applications. In conclusion, the success of the adaptation of the accounting profession in the digital era is largely determined by the readiness to develop technological and communication competencies.